2004
DOI: 10.1079/phn2003542
|View full text |Cite
|
Sign up to set email alerts
|

Large heterogeneity of the obesity epidemic in Danish adults

Abstract: Objective: To examine to what extent the obesity epidemic is a general phenomenon in adults by assessing the secular change, by birth cohort and age, in the prevalence of obesity and median body mass index (BMI) in Danish men and women measured between 1964 and 1994. Design: Multiple cross-sectional population surveys. Setting: The greater Copenhagen area of Denmark. Subjects: The study included 17 065 men (30 336 observations) and 13 417 women (24 065 observations), aged 20 -84 years. Main outcome measures: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…This notion is supported by the observed decrease after 2004, which may be taken as an indication that the pool of 'prevalent undiagnosed' cases is diminishing. Studies in the Danish population [9,10] have shown an increase in the incidences of overweight and obesity (although the increases were not dramatic), but have also shown that the increase is smaller in later-born cohorts, so this may be a further contributing factor. Because of the short time span after 2004, and since the break-point is chosen by examination of the data, the estimates for the two trends are those with maximally achievable difference (+5% before and −3% after), so the observed decrease should be viewed with caution.…”
Section: Discussionmentioning
confidence: 98%
“…This notion is supported by the observed decrease after 2004, which may be taken as an indication that the pool of 'prevalent undiagnosed' cases is diminishing. Studies in the Danish population [9,10] have shown an increase in the incidences of overweight and obesity (although the increases were not dramatic), but have also shown that the increase is smaller in later-born cohorts, so this may be a further contributing factor. Because of the short time span after 2004, and since the break-point is chosen by examination of the data, the estimates for the two trends are those with maximally achievable difference (+5% before and −3% after), so the observed decrease should be viewed with caution.…”
Section: Discussionmentioning
confidence: 98%
“…Due to heterogeneity in susceptibility to weight gain 1,25 and putative modifying effects of genes on the relationship between PA and weight change, 45 minutes of moderate PA may be enough to prevent weight gain in some, whereas 60 minutes might be too little in others.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Heterogeneity of time trends has been reported in some studies and this may indicate variations in susceptibility to obesity among population subsets 1 .…”
mentioning
confidence: 98%
“…In addition, sex differences in the historical development of obesity epidemics have also been seen. One study found that men had a steadily increasing prevalence of obesity in the 1970s and through up to the 2000s, whereas the prevalence of obesity in women remained stable until the 1990s after which an increase occurred similar to that in men (21) . Another study focusing on the years 1999-2004 showed significant increases in obesity in men but not in women (22) .…”
mentioning
confidence: 99%